Unraveling the role of Major Vault Protein as a novel immune-related biomarker that promotes the proliferation and migration in pancreatic adenocarcinoma - Wu, Xinyi; Hao, Leiyu; Lin, Jianghua; Guo, Xinyu; Luo, Yuping; Li, Chun (Frontiers in Immunology, 2024)
Background: Pancreatic adenocarcinoma (PAAD) is a formidable challenge in oncology research, with a complex pathogenesis that requires to be explored. Major Vault Protein (MVP) is the principal structural component of the vault complex, and its expression level is remarkably upregulated in various cancers. Extensive investigations have been conducted to explore the role of MVP in specific cancer contexts, yet the potential molecular mechanisms and biological functions of MVP in PAAD still remain considerably elusive. This study aims to explore the role of MVP as a novel immune-related biomarker in the pathogenesis and clinical treatment of PAAD. Methods: Gene expression data and clinical information were collected from TCGA, GTEx and GEO databases. Survival, prognostic and functional enrichment analysis were employed with R software. Immunological correlation analysis was performed using TIMER2.0, TIDE scores, TISIDB and TISCH. Epigenetic analysis was implemented by MethSurv, CPTAC, UALCAN, and cBioPortal. Drug analysis was conducted using Enrichr and CellMiner. Moreover, cellular experiments, like RNA interference, qRT-PCR, Western blot, cell cycle analysis, cell apoptosis analysis, colony formation assay, transwell assay, and wound healing assay, were performed for verifying the functional properties of MVP in the PAAD progression.We demonstrated an abnormally upregulated expression of MVP in PAAD tissues, which notably correlated with an adverse prognosis in PAAD patients. Functional analysis suggested the conceivable involvement of MVP in immune modulation, and immunotherapy. Additionally, we identified genetic alterations, reduced promoter methylation, and heightened phosphorylation in MVP. We also clarified Suloctidil and Tetradioxin as the most notable potential drugs targeting MVP in PAAD. Moreover, our experimental observations consistently highlighted the significant impact of MVP deficiency on impeding PAAD cell proliferation, inhibiting cell migration, and accelerating cell apoptosis. Interestingly, a potential link between MVP and ERK or AKT pathways was displayed, which opens new avenues for further exploration of the molecular mechanisms of MVP-targeted therapies in PAAD. Conclusions: This study systematically describes MVP as an immune-related biomarker with remarkable potential for predicting the prognosis, tumor progression and immunotherapeutic efficacy in PAAD.